Towards better-informed consent: Research with livestock-keepers and informal traders in East Africa - Cooper, Tarni L.; Kirino, Y.; Alonso, Silvia; Lindahl, Johanna F.; Grace, Delia (Elsevier, 2016)
With the rise of the One Health paradigm, ethicists have called for new research approaches, considering the interdependent relationships of humans, animals, and their environment. These relationships can be particularly complex within resource-poor, smallholder livestock systems, necessitating a rigorous informed-consent process. Little has been published on informed consent beyond human-subject research. This paper outlines two studies on informed consent, for research identifying diseases of animal and human importance, within smallholder livestock value chains.Firstly, a randomized independent-group study compared three communication tools (written, cartoons, and photographs) for informing 22 Tanzanian livestock-keepers before seeking their consent.A significant difference in comprehension and engagement in the informed-consent process was found between tools, and cartoons had the highest (i.e. best combined comprehension and engagement) scores.Most (21 out of 22) farmers answered half or more the questions correctly, but none were able to answer all questions. Comprehension testing allowed identification of common misunderstandings, such as immediate benefits the farmers would receive and the process to be used for relaying research results.Dialogue stimulated by cartoons and photographs allowed researchers to determine and respond to participants’ varied relationships with their livestock.The second study assessed preferred methods for indicating consent among informal-sector milk vendors in Nairobi, Kenya. Of consenting participants, 61% (140/230) indicated consent verbally, 39% (90/230)signed consent and none chose thumbprint. There was a significant enumerator-effect on both overall consent and the methods chosen.Several of these findings echo those published in human-medical research. Additionally, highlighted here is the importance of facilitating dialogue during the informed-consent process in One Health research, for a more nuanced understanding of relationships between humans, animals, and their environment. Also discussed is how a requirement to sign consent forms might limit consent among workers in informal markets, which are commonly studied in One Health research. We suggest expansion of these, and development of further, studies towards improving consent processes in One Health research.